2021
DOI: 10.1038/s41598-021-87499-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for myopia in Taiwanese diabetes mellitus patients: a multicenter case–control study in Taiwan

Abstract: This population-based retrospective cohort study investigated the prevalence of myopia among patients with Type 1 and Type 2 diabetes mellitus (DM) and evaluate risk factors for myopia in these groups. Records from 2000 to 2012 with at least one year of follow-up from the Taiwan National Health Insurance Research Database were included. This study included 35,538 patients with DM and 71,076 patients without DM. Patients with DM had a significantly higher adjusted hazard ratio for myopia in all age groups and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, studies on the relationship between diabetes and myopia remain controversial. Some studies found a positive relationship between diabetes and myopia [33,34], while no signi cant relationship was revealed in other studies [35,36]. The reasons for these diverse results may be the different blood glucose control levels of the patients included in the different studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, studies on the relationship between diabetes and myopia remain controversial. Some studies found a positive relationship between diabetes and myopia [33,34], while no signi cant relationship was revealed in other studies [35,36]. The reasons for these diverse results may be the different blood glucose control levels of the patients included in the different studies.…”
Section: Discussionmentioning
confidence: 98%
“…A study of children with diabetes 12 found no significant association between diabetes and myopia, although the prevalence of myopia may increase transiently in patients with diabetes at a younger age. However, a study in Taiwan 20 found a higher prevalence of myopia in the diabetic group than in the control group, but no significant difference was noted in high myopia prevalence. However, only few genetic and environmental factors have been definitively identified.…”
Section: Introductionmentioning
confidence: 86%
“…Myopia is a disease that is associated with both genetic and environmental factors. Despite extensive research over the past few decades, the mechanisms underlying myopia development and its related factors are still not fully understood.Previous observational studies have identi ed type 2 diabetes 7 , secondhand smoke exposure 8 , and BMI 9 as factors related to myopia.Those results may be biased by potential residual confounding.There is currently no research to substantiate the causal relationship between smoking initiation and myopia.Furthermore,previous studies do not establish a clear causal relationship between type 2 diabetes,BMI and myopia.…”
Section: Introductionmentioning
confidence: 99%